El mito de Atalanta e Hipómenes : fuentes grecolatinas y su pervivencia en la literatura española - Franco Durán, María Jesús (Anejos de Revista de literatura ;, 2016)
This study looks at the myth of Atalanta and Hippomenes in Spanish literature. It presents an overview of ancient, medieval, and modern mythographic sources, compares different Greek and Latin texts, and gives an analysis of the variants produced by Spanish authors. The texts discussed here bear witness to an underlying evolution of modes, rhetorical methods, sensibility, and ideology, as well as to the individual goals of each writer that help to shape this myth.